THE EFFECT OF POLYETHYLENEGLYCOL METHACRAYLATE-VINYLSULFONIC ACID GRAFT COPOLYMERS ON CALCIUM OXALATE CRYSTALLIZATION - Kirboga, Semra; Oner, Mualla (YILDIZ TECHNICAL UNIV, 2008)
The control of crystal growth and morphology of crystal is considerable importance in industrial crystallization and biomineralization. The formation of scales that is caused by calcium salt which has low solubility in heat exchanger or cooling tower process is lead to serious problems such as pollution, decreasing of heat transfer. In this study, the effects of polymeric additives on the crystallization of calcium oxalate monohydarate have been investigated in aqueous solutions. Vinylsulfonic acid homopolymer and polyethyleneglycol methacrylate-co-vinylsulfonic acid graft copolymers, having different number of sulfonic acid group, have been used as additives. The effect of polymers on the rate of precipitation of calcium oxalate has been determined by recording the decrease of solution conductivity as a function of time. The polymer architecture and acid contents of the polymers were found to be important parameters in inhibition of calcium oxalate crystallization.
Keywords: Calcium oxalate crystallization; polymers; inhibitors; Engineering